The participatory economy: an evolutionary hypothesis and a strategy for development - Vanek, Jaroslav (Ithaca: Cornell University Press, 1971)
Besides economics the subject matter of this book bears or borders on several fields including history, sociology, political science, philosophy, and even psychology. This small volume ought therefore to be taken as a general essay and not as a scholarly product of any of the fields noted.
Includes bibliographical references.
rpm 25/10/2017
Loans
Keywords: Management; Capitlism; Employee ownership; Yugoslavia